Comparision of modified and conventional delta-shaped gastroduodenostomy in totally laparoscopic surgery - Huang, Chang-Ming (Baishideng Publishing Group Inc, 2014)
AIM: To evaluate the safety and feasibility of a modified delta-shaped gastroduodenostomy (DSG) in totally laparoscopic distal gastrectomy (TLDG). METHODS: We performed a case-control study enrolling 63 patients with distal gastric cancer (GC) undergoing TLDG with a DSG from January 2013 to June 2013. Twenty-two patients underwent a conventional DSG (Con-Group), whereas the other 41 patients underwent a modified version of the DSG (Mod-Group). The modified procedure required only the instruments of the surgeon and assistant to complete the involution of the common stab incision and to completely resect the duodenal cutting edge, resulting in an anastomosis with an inverted T-shaped appearance. The clinicopathological characteristics, surgical outcomes, anastomosis time and complications of the two groups were retrospectively analyzed using a prospectively maintained comprehensive database. RESULTS: DSG procedures were successfully completed in all of the patients with histologically complete (R0) resections, and none of these patients required conversion to open surgery. The clinicopathological characteristics of the two groups were similar. There were no significant differences between the groups in the operative time, intraoperative blood loss, extension of the lymph node (LN) dissection and number of dissected LNs (150.8 ± 21.6 min vs 143.4 ± 23.4 min, P = 0.225 for the operative time; 26.8 ± 11.3 min vs 30.6 ± 14.8 mL, P = 0.157 for the intraoperative blood loss; 4/18 vs 3/38, P = 0.375 for the extension of the LN dissection; and 43.9 ± 13.4 vs 39.5 ± 11.5 per case, P = 0.151 for the number of dissected LNs). The anastomosis time, however, was significantly shorter in the Mod-Group than in the Con-Group (13.9 ± 2.8 min vs 23.9 ± 5.6 min, P = 0.000). The postoperative outcomes, including the times to out-of-bed activities, first flatus, resumption of soft diet and postoperative hospital stay, as well as the anastomosis size, did not differ significantly (1.9 ± 0.6 d vs 2.3 ± 1.5 d, P = 0.228 for the time to out-of-bed activities; 3.2 ± 0.9 d vs 3.5 ± 1.3 d, P = 0.295 for the first flatus time; 7.5 ± 0.8 d vs 8.1 ± 4.3 d, P = 0.489 for the resumption of a soft diet time; 14.3 ± 10.6 d vs 11.5 ± 4.9 d, P = 0.148 for the postoperative hospital stay; and 30.5 ± 3.6 mm vs 30.1 ± 4.0 mm, P = 0.730 for the anastomosis size). One patient with minor anastomotic leakage in the Con-Group was managed conservatively; no other patients experienced any complications around the anastomosis. The operative complication rates were similar in the Con- and Mod-Groups (9.1% vs 7.3%, P = 1.000). CONCLUSION: The modified DSG, an alternative reconstruction in TLDG for GC, is technically safe and feasible, with a simpler process that reduces the anastomosis time.